Health Literacy dengan Tingkat Kecemasan Pasien Covid-19 - Weni Wulandari; Yuliza, Emi; Herlina, Irma (MPI Press, 2022)
Introduction: Health Literacy is a parameter or instrument for measuring the level of anxiety of Covid-19 patients in the inpatient room at the Depok HGA Hospital. Purpose: The purpose of this study was to determine the relationship between patient health literacy and the anxiety level of Covid-19 patients in the inpatient room at HGA Depok Hospital in 2021. Methods: This type of research is quantitative with a Cross-Sectional approach. The population in this study were Covid-19 patients in the inpatient room at HGA Depok Hospital and the sample needed in this study was 78 respondents using the purposive sampling method. Research data analysis using Chi-Square test. Results: Based on the results of the study, the picture of the patient's health literacy was poor with 41 respondents (52.6%). The description of the level of anxiety obtained moderate anxiety as many as 31 respondents (39.7%). The results of statistical tests are known with the p-value = 0.005 < 0.05. Conclusion: There is a relationship between patient health literacy and the level of anxiety of Covid-19 patients in the inpatient room at HGA Depok Hospital in 2021.